What Is the Added Value of DWI Compared with Structured Assessment of BI-RADS Criteria by the Kaiser Score? A Systematic Review and Meta-analysis - Dietzel, Matthias; Baltzer, Pascal A.T.; Vatteroni, Giulia (Investigative Radiology, 2024)
Objective This systematic review and meta-analysis investigated the added value of DWI compared with the structured assessment of BI-RADS criteria using the Kaiser score. Materials and Methods Articles published in English until May 2024 were included. Two independent reviewers extracted data on the characteristics of studies evaluating the added value of DWI to distinguish benign from malignant breast lesions compared with structured assessment of the BI-RADS criteria. Using bivariate random-effects models, the sensitivity and specificity were calculated. I2 statistics, Deek's funnel plot asymmetry test for publication bias, and meta-regression were applied for the data analysis. Results Five studies comprising 1005 malignant and 846 benign lesions were eligible for data synthesis. The pooled sensitivity and specificity estimates of structured BI-RADS assessment were 95.7% (95% confidence interval [CI], 92.6%-97.5%) and 68.7% (95% CI, 60.9%-75.6%), respectively. Adding DWI to the structured BI-RADS assessment achieved a pooled sensitivity of 94.4% (95% CI, 90.5%-96.7%) and a pooled specificity of 74.9% (95% CI, 68.8%-80.2%). Adding DWI to the structured BI-RADS assessment significantly changed neither the sensitivity (P = 0.52) nor the specificity (P = 0.20). Conclusions This systematic review and meta-analysis revealed only a limited, statistically nonsignificant added value of DWI compared with the structured assessment of BI-RADS criteria using the Kaiser score.
CRIS-Team Scopus Importer:2024-11-01
Keywords: apparent diffusion coefficient; breast imaging reporting and data system; breast neoplasms; clinical decision-making; decision support systems; clinical; magnetic resonance imaging